Dysregulated noradrenergic response is associated with symptom severity in individuals with schizophrenia - Pelegrino, Ana; Guimaraes, Anna Luiza; Sena, Walter; Emele, Nwabunwanne; Scoriels, Linda; Panizzutti, Rogerio (Frontiers in Psychiatry, 2023)
Introduction The locus coeruleus-noradrenaline (LC-NA) system is involved in a wide range of cognitive functions and may be altered in schizophrenia. A non-invasive method to indirectly measure LC activity is task-evoked pupillary response. Individuals with schizophrenia present reduced pupil dilation compared to healthy subjects, particularly when task demand increases. However, the extent to which alteration in LC activity contributes to schizophrenia symptomatology remains largely unexplored. We aimed to investigate the association between symptomatology, cognition, and noradrenergic response in individuals with schizophrenia. Methods We assessed task-evoked pupil dilation during a pro- and antisaccade task in 23 individuals with schizophrenia and 28 healthy subjects. Results Both groups showed similar preparatory pupil dilation during prosaccade trials, but individuals with schizophrenia showed significantly lower pupil dilation compared to healthy subjects in antisaccade trials. Importantly, reduced preparatory pupil dilation for antisaccade trials was associated with worse general symptomatology in individuals with schizophrenia. Discussion Our findings suggest that changes in LC-NA activity – measured by task-evoked pupil dilation – when task demand increases is associated with schizophrenia symptoms. Interventions targeting the modulation of noradrenergic responses may be suitable candidates to reduce schizophrenia symptomatology.